STUDY OF THE WORK "GULISTAN" AND ITS TRANSLATIONS (Scientific journal of the Fergana State University, 2024)
Saadi Shirazi wrote many works during his life. The work "Gulistan" has a special place among them. This work attracted the attention of the peoples of the world already in the Middle Ages. Its research began with its translation into different languages of the world. In later periods, the work was studied by scientists from the point of view of linguistics, literary studies, philosophy, political science, and pedagogy. The article talks about the translations of the work into different languages and the scientific research conducted on the work.